Bootstrapped : liberating ourselves from the American Dream - Quart, Alissa (Ecco, an imprint of HarperCollinsPublishers, 2023)
Examines the American obsession with self-reliance and how it has led to inequality, self-blame, and shifted the responsibility for survival onto the backs of ordinary people.